Cangrejos braquiuros (Brachyura) del arrecife de Cabo Pulmo-Los Frailes y alrededores, Golfo de California, México - García-Madrigal, María del Socorro (1999)
Fragments of the coral Pocillopora elegans collected in 1988 and 1989 produced 281 specimens of brachyurans. There were 30 species and subspecies in eight families, and 22 are new records for the Cabo Pulmo-Los Frailes reef. Including earlier records, there are now 61 species and subspecies (19 families) from the area. Majidae had the largest number of species (23), followed by Panopeidae (9), and Xanthidae (6). Most abundant were Trapezia ferruginea (71 specimens), Theleophrys cristulipes (39) and Microcassiope xantusii xantusii (29). The species were sorted out in four zoogeographic groups: Indopacific (8.5%), Amphiamerican (5.1%), Eastern Pacific (76.3%), and Mexican Pacific endemics (10.1%). The reef represents only 0.004% of the Gulf area but harbors 21% of all species recorded from the gulf of California, western coast of Baja California Sur and exclusive economic zone of Nayarit and Sinaloa.